Sprint skating profile of competitive male bandy players: determination of positional differences and playing level - van den Tillaar, Roland; Pojskic, Haris; Andersson, Håkan (Frontiers in Physiology, 2023)
This study aimed to compare sprint skating profile characteristics of the different playing positions of junior and senior bandy players. In total, 111 male national-level bandy players (age: 20.7 ± 5.0 years, height: 1.80 ± 0.05 m, body mass: 76.4 ± 0.4 kg, training experience: 13.8 ± 5.0 yrs) were tested on their sprint skating profile over 80 m. The main findings were that no differences between positions were found in sprint skating performance (speed and acceleration), but that elite players were in general heavier (p < 0.05) than junior players (80.0 ± 7.1 vs. 73.1 ± 8.1 kg), they could accelerate faster (2.96 ± 0.22 vs. 2.81 ± 0.28 m/s2), and they reached a higher velocity (10.83 ± 0.37 vs. 10.24 ± 0.42 m/s) earlier over 80 m than the junior players. This implies that junior level players should spend more time in power and sprint training to meet the specific demands of playing at a higher, elite level.